Metabolomics identifies plasma biomarkers of localized radiation injury - Lucie Ancel; Stéphane Grison; Olivier Gabillot; Jules Gueguen; Ljubica Svilar; Bernard Le Guen; Gaëtan Gruel; Marc Benderitter; Jean-Charles Martin; Maâmar Souidi; Radia Tamarat; Stéphane Flamant; et al. (Scientific Reports)
Abstract A radiological accident may result in the development of a local skin radiation injury (LRI) which may evolve, depending on the dose, from dry desquamation to deep ulceration and necrosis through unpredictable inflammatory waves. Therefore, early diagnosis of victims of LRI is crucial for improving medical care efficiency. This preclinical study aims to identify circulating metabolites as biomarkers associated with LRI using a C57BL/6J mouse model of hind limb irradiation. More precisely, two independent mice cohorts were used to conduct a broad-spectrum profiling study followed by a suspect screening analysis performed on plasma metabolites by mass spectrometry. An integrative analysis was conducted through a multi-block sparse partial least square discriminant analysis (sPLS-DA) to establish multi-scale correlations between specific metabolites levels and biological, physiological (injury severity), and functional parameters (skin perfusion). The identified biomarker signature consists in a 6-metabolite panel including putrescine, uracil, 2,3-dihydroxybenzoate, 3-hydroxybenzoate, L-alanine and pyroglutamate, that can discriminate mice according to radiation dose and injury severity. Our results demonstrate relevant molecular signature associated with LRI in mice and support the use of plasma metabolites as suitable molecular biomarkers for LRI prognosis and diagnosis.